Exploring the morphological diversity of Patagonian clades of Phymaturus (Iguania: Liolaemidae): integrative study and the description of two new species - Lobo, Fernando (2022)
In the present contribution, we revisited the taxonomy and phylogenetic relationships within the somuncurensis and spurcus clades of Phymaturus lizards. Based on 296 morphological characters and DNA sequences, we evaluated the taxonomic species status of each clade and of two populations sampled in a field trip. Based on this evidence, we describe two new taxa for the genus. We also studied the species recently described for Chubut province, we analyzed their phylogenetic relationships, and compared them with other Patagonian species. Here, we provide data of color in life, squamation, and measurements, and compare in detail the new taxa to other members of their respective clades. We found that the somuncurensis clade comprises nine species (plus two other candidate ones) distributed mostly peripherally to the Somuncurá plateau, and present on the margins of it in isolated creeks and small mountain chains. Recent molecular studies arrived to different conclusions about the taxonomic validity of closely related species of the spurcus clade of Phymaturus lizards. We decided to revisit this group and contribute with a more complete analysis for two reasons: none of these studies revisited carefully the overall morphology and type series, and the only article that revisited this complex of species studied only one color pattern character, without providing voucher information (matching color types-collection specimens-DNA samples-sites). We studied the type series of all species, revisited characters taken from squamation and measurements, revised the color pattern of all terminals, and performed statistical analysis. Our results discovered statistically significant characters, which provide enough morphological support to consider all species of the group as valid in congruence to the multilocus analysis that combined mitochondrial and nuclear data published recently. We also provide discrete color pattern characters that help to adequately differentiate these species.